2004
DOI: 10.1038/sj.ejcn.1602007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different nutritional feeds on the postprandial glucose response in healthy volunteers and patients with type II diabetes

Abstract: Objective: Assessment of postprandial glycaemic response to four nutritional feeds with different macronutrient and fibre composition. Design: A randomized, double-blind, crossover study. Setting: University of Maastricht, the Netherlands. Subjects: A total of 10 healthy volunteers and 10 patients with type II diabetes. Interventions: Subjects received 200 kcal of four enteral nutrition products (two standard products and two diabetes-specific products). Fasting and postprandial plasma glucose were measured fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
2
29
0
3
Order By: Relevance
“…majority of the studies the diabetesspecific formulas showed lower triglyceride concentrations than the standard formulas, the combined data from four RCTs (14,38,44,45) indicated no significant effect (effect size Ϫ0.11 [95%CI Ϫ0.5 to 0.28], r ϭ 0; effect size Ϫ0.13 [Ϫ0.53 to 0.26], r ϭ 0.5) ( Table 1). Furthermore, two other long-term RCTs (49,54) reported no significant effect of diabetes-specific versus standard formulas on triglycerides, whereas the findings of a short-term RCT were unclear (48). None of these studies provided any detailed data.…”
Section: Lipidemia (Total Cholesterol Hdl and Triglycerides)mentioning
confidence: 99%
See 1 more Smart Citation
“…majority of the studies the diabetesspecific formulas showed lower triglyceride concentrations than the standard formulas, the combined data from four RCTs (14,38,44,45) indicated no significant effect (effect size Ϫ0.11 [95%CI Ϫ0.5 to 0.28], r ϭ 0; effect size Ϫ0.13 [Ϫ0.53 to 0.26], r ϭ 0.5) ( Table 1). Furthermore, two other long-term RCTs (49,54) reported no significant effect of diabetes-specific versus standard formulas on triglycerides, whereas the findings of a short-term RCT were unclear (48). None of these studies provided any detailed data.…”
Section: Lipidemia (Total Cholesterol Hdl and Triglycerides)mentioning
confidence: 99%
“…However, the methodology of individual RCTs was often poorly described (with regard to methods of randomization, blinding, and recording number of drop-outs), with only three studies (45,47,48) scoring the top grade of five on the Jadad scale (34). The remaining RCTs scored four (46,49), three (38,54), two (11,14,39 -44,50,52), or one (51,53).…”
Section: Overall Search Findingsmentioning
confidence: 99%
“…Comme attendu, avec ces modifications, on observe une diminution de la réponse glycémique chez le sujet diabétique comme chez le sujet sain [18]. Pour une même quantité de glucides, les produits pour diabétiques ont un IG significativement plus faible (IG = 19,4 ± 1,8 vs 42,1 ± 5,9).…”
Section: Charge Glycémique Des Mélanges Pour Neunclassified
“…Pour une même quantité de glucides, les produits pour diabétiques ont un IG significativement plus faible (IG = 19,4 ± 1,8 vs 42,1 ± 5,9). Les produits nutritifs standards ont des IG considérés comme faibles (< 55) ou modérés (55 à 70) [18].…”
Section: Charge Glycémique Des Mélanges Pour Neunclassified
See 1 more Smart Citation